2013
DOI: 10.1039/c3nr33962a
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured graphene/Fe3O4 incorporated polyaniline as a high performance shield against electromagnetic pollution

Abstract: The development of high-performance shielding materials against electromagnetic pollution requires mobile charge carriers and magnetic dipoles. Herein, we meet the challenge by building a three-dimensional (3D) nanostructure consisting of chemically modified graphene/Fe3O4(GF) incorporated polyaniline. Intercalated GF was synthesized by the in situ generation of Fe3O4 nanoparticles in a graphene oxide suspension followed by hydrazine reduction, and further in situ polymerization with aniline to form a polyanil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
267
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 514 publications
(274 citation statements)
references
References 45 publications
6
267
0
1
Order By: Relevance
“…During the past decade, improvements in EMI shielding effectiveness (SE) have been achieved by introducing carbon materials, such as carbon black, carbon ber, exfoliated graphite, graphite, yash, carbon nanotubes (CNTs) and even now multilayer graphene. 12,[15][16][17][18][19] To improve the properties of the PANI, Saini et al 15 developed PANI based composite by in situ emulsion pathway technique with a different ratio of graphite and PANI. It is reported that by incorporating 15.6 wt% of graphite in PANI, the ultimate composite possesses electrical conductivity 12.5 S cm À1 and total EMI-SE is reached up to À33.6 dB in the X-band frequency region .…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, improvements in EMI shielding effectiveness (SE) have been achieved by introducing carbon materials, such as carbon black, carbon ber, exfoliated graphite, graphite, yash, carbon nanotubes (CNTs) and even now multilayer graphene. 12,[15][16][17][18][19] To improve the properties of the PANI, Saini et al 15 developed PANI based composite by in situ emulsion pathway technique with a different ratio of graphite and PANI. It is reported that by incorporating 15.6 wt% of graphite in PANI, the ultimate composite possesses electrical conductivity 12.5 S cm À1 and total EMI-SE is reached up to À33.6 dB in the X-band frequency region .…”
Section: Introductionmentioning
confidence: 99%
“…When the total EMI shielding effectiveness of the material is more than À10 dB, then loss due to multiple reections (SE M ) becomes negligible and can be neglected. 34,38,39 Thus, the total shielding effectiveness (SE T ) can be expressed as…”
Section: Microwave Shielding Effectivenessmentioning
confidence: 99%
“…To overcome the aforementioned problems, researchers have since developed hybrid materials that combine several shielding materials to offset respective limitation of the materials while still retaining its enhanced shielding properties. Various combinations of materials with optimum shielding capabilities have since been developed [7,9,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, hexagonal ferrites have long been known to possess salient properties such as good chemical stability [2], large crystal anisotropy [3,4], and big values of permeability [5,6], enabling it to exhibit good electromagnetic wave absorbing properties. The discovery of its high electrical conductivity have renewed interests in the intrinsically conducting polymer (ICP), polyaniline (PANI), and its possible applications for microwave absorption [7][8][9]. Carbon based shielding materials have seen widespread adoption in various fields of application due to their light weight and are known to show good electrical properties [10].…”
Section: Introductionmentioning
confidence: 99%